Implementasi Konseling CBT dengan Teknik Cognitive Restructuring untuk Peningkatan Motivasi Belajar pada Peserta Didik - Munir, Ah. Fahri; Fahira, Ihza Chaidaratul; Kaesti, Mutiarani R. D. E; Aiwani, Aisyiah; Nate, Mahara Pinte; Hasanah, Binti Uswatun (Prodi Bimbingan Konseling FKIP UNDANA, 2024)
The problem of learning motivation is a problem that many students experience. In response to this, the researcher aims to conduct research using a library research design related to the Implementation of CBT Counseling with Cognitive Restructuring Techniques to Increase Learning Motivation in Students. The results obtained from the researchers' search are that CBT counseling using cognitive restructuring techniques is a form of service that will be carried out to intervene with low learning motivation. Cognitive restructuring is a service that can assist students in improving the concept of life and can change the rational mindset of an individual. Cognitive restructuring technique is a process of identifying and evaluating cognitive in a more realistic, precise and adaptive way of thinking. Low motivation to learn can cause a person to be unable to focus on following the lessons in class and may even have no interest in the learning process. Counseling cognitive behavior therapy with cognitive restructuring techniques can have an impact so that new behaviors emerge, in this study namely increasing motivation to learn in students. This is because this cognitive restructuring technique has the main goal, namely to be able to change irrational thoughts and make them have rational thoughts.